Biology Learning Management Contain Using Character Education With T-PACK Through Project Based Learning (PBL) Model - Pujianti, Pujianti; Kardoyo, Kardoyo; Utanto, Yuli (Educational Management, 2021)
The purpose of the study was to determine the planning, organization, implementation, evaluation, and learning outcomes of biology with character education with Technological Pedagogical Content Knowledge (T-PACK) approach through PBL model at SMAN 8 Semarang. Covid-19 virus has spread to infect almost all countries in the world. Learning management studies show the need for state readiness in the case of a pandemic in the direction of education. Learning management during covid-19 pandemic was carried out with Project Based Learning (PBL). One of the learning managements that applied was T-PACK model. Based on the results of the previous research, there was very little research on T-PACK development related to character education. The approach in this study was interdisciplinary qualitative with phenomenological approach. The design research was case study. Informants are 2 biology teachers. The technique of checking the validity of the data using Degree of Trust (Credibility), Transferability, Defendability, and Certainty (Confirmability). Data that has been collected from in-depth interviews with informants was processed and then data analysis was carried out. The stages of data analysis have 4 main components, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the planning, organization, implementation, evaluation, and learning outcomes of biology contained character education with the T-PACK approach through PBL model. The results of this study are expected to be source and study material in increasing knowledge about management of biology learning with character education with help of T-PACK through the PBL model.